Stop signals decrease choices for palatable foods through decreased food evaluation - Veling, Harm; Aarts, Henk; Stroebe, Wolfgang (Frontiers in Psychology, 2013)
The present study explores whether presenting specific palatable foods in close temporal proximity of stop signals in a go/no-go task decreases subsequent evaluations of such foods among participants with a relatively high appetite. Furthermore, we tested whether any decreased evaluations could mediate subsequent food choice. Participants first received a go/no-go task in which palatable foods were consistently linked to go cues or no-go cues within participants. Next, evaluation of the palatable foods was measured as well as food choice. Replicating previous work, results show that among participants with a relatively high appetite palatable foods associated with no-go cues are less often chosen as snacks compared to when these foods are associated with go cues, whereas this manipulation did not affect participants with a relatively low appetite. Moreover, this effect was completely mediated by decreased evaluation of the palatable foods that had been associated with the no-go cues, whereas evaluation of the foods associated with go cues did not mediate this effect. Results further showed that the devaluation effect of foods associated with no-go cues was independent of the amount of pairings (4 vs. 12 vs. 24) with the no-go cues. The current findings suggest that decreased food evaluation is a mechanism that explains effects of stop signals on food choice.